2018
DOI: 10.1007/s12640-017-9861-3
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Pattern and Crosstalk of Necroptosis Markers with Autophagy and Apoptosis Associated Proteins in Ischemic Hippocampus

Abstract: Necroptosis, a novel type of programmed cell death, has been recently implicated as a possible mechanism for cerebral ischemia-reperfusion (I/R) injury. We herein studied time-dependent changes of necroptosis markers along with apoptosis- and autophagy-associated proteins in rat hippocampus at 1, 3, 6, 12, 24, and 48 h after global cerebral I/R injury. Furthermore, to determine the cross talk between autophagy and necroptosis, we examined the effects of pretreatment with bafilomycin-A1 (Baf-A1), as a late-stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 88 publications
1
21
0
Order By: Relevance
“…In order to accelerate the process of aortic calcification, rats undergoing renal ablation surgery were administered with a standard high-phosphorus diet (1.2% Pi). Two weeks after 5/6 Nx, eight rats were randomly selected as the CKD group (CKD rats without other treatments), and 40 CKD rats were injected with corresponding adenoviruses of 0.3 nmol/μ autophagy activator Rapamycin (RAPA; 5 μl) or 2 nmol/μl autophagy inhibitor bafilomycin A1 (Baf-A1; 5 μl), or dimethyl sulfoxide (DMSO; 5 μl; Lana et al, 2017;Ryan et al, 2018) via tail vein according to the grouping as follows:…”
Section: Ethics Statementmentioning
confidence: 99%
“…In order to accelerate the process of aortic calcification, rats undergoing renal ablation surgery were administered with a standard high-phosphorus diet (1.2% Pi). Two weeks after 5/6 Nx, eight rats were randomly selected as the CKD group (CKD rats without other treatments), and 40 CKD rats were injected with corresponding adenoviruses of 0.3 nmol/μ autophagy activator Rapamycin (RAPA; 5 μl) or 2 nmol/μl autophagy inhibitor bafilomycin A1 (Baf-A1; 5 μl), or dimethyl sulfoxide (DMSO; 5 μl; Lana et al, 2017;Ryan et al, 2018) via tail vein according to the grouping as follows:…”
Section: Ethics Statementmentioning
confidence: 99%
“…adiponectin (aPn), also known as GBP-28, apM1, adipoQ and acrp30, is a novel adipokine that maintains insulin responsiveness, stimulates mitochondrial biogenesis, inhibits inflammatory response and modulates autophagy and apoptosis in different disease models (12,13). a clinical study has revealed that the level of aPn is independently associated with mortality and low plasma aPn is related to an increased risk of 5-year mortality following the first-ever ischemic stroke in humans (14).…”
Section: Introductionmentioning
confidence: 99%
“…e present study expanded our previous research and investigated the potential neuroprotective mechanisms of GTPs concerning endogenous antioxidation and ER stress. e imbalance of oxidation and antioxidation is a direct reason for deficits of neurological functions and high mortality during CIRI [24,25]. GTPs possess higher antioxidant activity than vitamin E and vitamin C [26,27].…”
Section: Discussionmentioning
confidence: 99%